Qualitative systematic review on the lived experience of functional neurological disorder - Loyola McLean; Andrea Szasz; Anthony Korner (BMJ Neurology Open)
Objectives Functional neurological disorder (FND) is a complex disorder, recently attracting much research into aetiology and treatment. However, there is limited research on the patient’s lived experience. This paper addresses this gap to ask: ‘What is the subjective life experience of adult patients living with FND?’Methods From 1980 to 2020, Medline, PsycInfo, Scopus, Science Direct, PubMed, CINAHL and Embase were searched for English language qualitative adult research. The disciplines used general medicine, psychiatry, physiotherapy, nursing, neurology, psychosomatic medicine and occupational therapy. The qualitative literature search included book chapters, theses, fellowship reports and conference articles as well as peer-reviewed scientific journals.The Critical Appraisal Skills Programme tool was used to assess 33 papers, with eight papers included in the final synthesis. Nine additional papers, suggested during review, were evaluated but excluded from synthesis, though incorporated elsewhere in the paper. Two authors used an integrative immersion approach to identify the literature’s main themes using line-by-line and top-down methods.Results Eight main themes were identified: lost, body–mind dualism, preceding stressful events, relatedness, stigma, the battle or fight, the burden and losses of the illness and trust versus mistrust. From these emerged a central overarching theme of relationally regulated selves, which posits the essence of the lived experience of FND as responding to stressful experiences within a relational, regulatory context.Conclusions The prevalent themes give valuable insight into the lived experience of FND and the impact of stressors, past and present, and the relational environment in the development of and recovery from the disorder. Further research is needed to support the formulation of the patient experience and cocreated recovery pathways.